Unravelling the molecular mechanisms and immune landscape of vitiligo: a comprehensive bioinformatics study on melanogenesis-related genes - Binxi Ma; Xiao Wang (Annals of Human Biology)
Background Vitiligo is an autoimmune disorder marked by melanocyte destruction and skin depigmentation.Aim To explore the molecular mechanisms underlying melanogenesis and their link to vitiligo.Subjects and methods We analysed three vitiligo-related datasets, correcting for batch effects with ComBat. Key melanogenesis genes were pinpointed using LASSO and logistic regression, and a nomogram was developed. The immune microenvironment was evaluated by ssGSEA, and correlations between gene expression, melanogenesis pathways, and immune cell infiltration were examined.Results We identified 2,405 DEGs, with 960 up-regulated and 1,445 down-regulated genes in vitiligo samples. GSVA indicated significant disturbances in melanogenesis pathways. ssGSEA revealed reduced activity in REACTOME_MELANIN_BIOSYNTHESIS and KEGG_MELANOGENESIS pathways. Three key diagnostic genes (CALM2, KIT, OCA2) were found and used to build a highly accurate predictive nomogram. Immune cell analysis showed increased T helper and Th2 cells in vitiligo, correlating with both diagnostic genes and melanogenic pathways.Conclusion This study identifies crucial melanogenesis-related genes and provides a predictive model for vitiligo risk. It underscores the relationship between impaired melanogenesis and immune cell infiltration, suggesting potential therapeutic targets.